Systematic Literature Review: Strategi Pembelajaran Berbantuan Media Pembelajaran IPAS dalam Meningkatkan Minat dan Hasil Belajar Siswa Kelas IV - Yulianti Hasan, Eko Handoyo; Tri Joko Raharjo, Sri Sumartiningsih, Agus Yuwono (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This literature review aims to analyze how strategies for improving learning outcomes and interest in learning are assisted by learning media in science learning. In answering the learning problems of fourth grade elementary school students, various learning strategies have been proven to increase student interest and learning outcomes. Using the literature review method in PRISMA with the keywords "Learning Outcomes, Learning Interests, Elementary School, Pancaindra", this research analyzes articles from 2020 to 2024 to evaluate the effectiveness of learning strategies assisted by learning media on students' interests and learning outcomes, especially in Pancindra class science material. IV Elementary School. The results of article analysis show that in the search results of 200 articles in the Google Scholar database, various learning strategies, learning media, and LKPD-based assessments have an influence on learning outcomes and interest. However, the effectiveness of applying a particular method in one class may not necessarily be successful in other research contexts, so it is necessary to consider learning media that can accommodate student characteristics and material characteristics. Meanwhile, in fourth grade elementary school, the application of Quartet media to various materials is consistently able to improve students' learning outcomes and interest with various characteristics, but has not been studied in more depth in the five-sensory material. This research concludes that the success of a learning approach is largely determined by its suitability to student characteristics. In particular, the Quartet Card media has not been explored further, even though its application in other research has shown significant results on various student characteristics, so these findings are expected to encourage the application of the Quartet Card to review how effective it is in fourth grade elementary school sensory material.